2009
DOI: 10.1016/j.biopsych.2009.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Modulation of Cerebral Glucose Metabolism in Depressed Older Adults

Abstract: Background-Monoamine dysfunction, particularly of the serotonin system, has been the dominant hypothesis guiding research and treatment development in affective disorders. The majority of research has been performed in mid-life depressed adults. The importance of understanding the neurobiology of depression in older adults is underscored by increased rates of mortality and completed suicide and an increased risk of Alzheimer's dementia. To evaluate the dynamic response of the serotonin system, the acute effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 51 publications
2
52
0
Order By: Relevance
“…Furthermore, between-subject differences in medication existed, and it is known that selective reuptake inhibitors may induce metabolic decreases in the ACC, middle temporal cortex, precuneus, and parahippocampal region (37). However, since medication was kept low and stable during the imaging period, medication is unlikely to have been a confounder in the current results.…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, between-subject differences in medication existed, and it is known that selective reuptake inhibitors may induce metabolic decreases in the ACC, middle temporal cortex, precuneus, and parahippocampal region (37). However, since medication was kept low and stable during the imaging period, medication is unlikely to have been a confounder in the current results.…”
Section: Discussionmentioning
confidence: 61%
“…Aß(−) MCI subjects positive to depressive symptoms were mostly inconspicuous with regard to FDG metabolism. These results likely explain the inconsistent results in previous FDG-PET studies regarding late-life depression where Aß status was not hitherto considered: Either hypermetabolism [11-13, 24] or hypometabolism [14-17] have been reported in late-life depressed subjects both in cognitively preserved, and impaired and AD patients. Moreover, PVEC was not applied in these FDG-PET studies investigating this topic, such that atrophy, as may occur in depressed subjects [37, 38], may have resulted in spurious findings of hypometabolism.…”
Section: Discussionmentioning
confidence: 77%
“…Prior investigations regarding the link between depression and brain amyloidosis have mainly focused on subjects with remitted earlier depressive episodes [8-10], mostly finding elevated β-amyloid levels. Despite these roughly consistent amyloid PET findings, there is less concordance in [ 18 F]-fluorodeoxyglucose (FDG) PET studies in depressed subjects, which have shown regions of hypermetabolism [11-13] or hypometabolism [14-17]. …”
Section: Introductionmentioning
confidence: 99%
“…To evaluate significant differences, we used an approach with the peak threshold set at P ϭ .001 (uncorrected) for whole brain regions. 13,14 For hypothesis generation, we reported only clusters that survived an FDR correction at P Ͻ .05. Significant regions were localized by Talairach Daemon software (http://software.incf.org/software/talairach-daemon) after using a MNI-to-Talairach conversion tool.…”
Section: Discussionmentioning
confidence: 99%